1995
DOI: 10.1111/j.1476-5381.1995.tb15082.x
|View full text |Cite
|
Sign up to set email alerts
|

2‐Naphthalenesulphanyl‐L‐aspartyl‐2‐(phenethyl) amide (2‐NAP) and food intake in rats: evidence that endogenous peripheral CCK does not play a major role as a satiety factor

Abstract: 1The demonstration that systemic administration of the CCKA receptor antagonist, devazepide, increases food intake in rats has provided the strongest support for the hypothesis that endogenous peripherally released cholecystokinin (CCK) acts as a satiety factor. However, interpretation of these results has been confounded by the fact that devazepide can enter the brain from the systemic circulation and may increase food intake by a central action. The present study was therefore undertaken to confirm the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In our experimental system, administration of devazepide alone resulted in a significant 23 h augmentation of food intake compared to controls. This observation is consistent with the hyperphagia originally reported in a variety of animal species under a number of different feeding schedules and sustains the hypothesis that endogenous CCK plays a role in the control of food intake through the activation of CCK 1 receptors (Hewson et al , 1988; Ebenezer et al , 1990; Bado et al , 1991; Weatherford et al , 1993; Covasa and Forbes, 1994; Ebenezer and Baldwin, 1995). The present study also showed that coadministration of devazepide (100 μ g kg −1 ) with the PEGylated CCK 9 (6 μ g kg −1 ) completely abolished the anorectic effect of PEG‐CCK 9 over the 23 h measurement period, showing that CCK 1 receptors are involved in food intake reduction induced by PEGylated CCK 9 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our experimental system, administration of devazepide alone resulted in a significant 23 h augmentation of food intake compared to controls. This observation is consistent with the hyperphagia originally reported in a variety of animal species under a number of different feeding schedules and sustains the hypothesis that endogenous CCK plays a role in the control of food intake through the activation of CCK 1 receptors (Hewson et al , 1988; Ebenezer et al , 1990; Bado et al , 1991; Weatherford et al , 1993; Covasa and Forbes, 1994; Ebenezer and Baldwin, 1995). The present study also showed that coadministration of devazepide (100 μ g kg −1 ) with the PEGylated CCK 9 (6 μ g kg −1 ) completely abolished the anorectic effect of PEG‐CCK 9 over the 23 h measurement period, showing that CCK 1 receptors are involved in food intake reduction induced by PEGylated CCK 9 .…”
Section: Discussionsupporting
confidence: 91%
“…(2003) suggested that the ineffectiveness of A‐70104 in these studies of Ebenezer and Parrot could be ascribed to the small doses used. In the present study, we used a dose of 3 mg kg −1 of 2‐NAP, which is reported to be sufficient to block the effects of exogenous peripheral CCK (Ebenezer and Baldwin, 1995), suggesting that this dose should also be sufficient to block the effects of the endogenous peripheral CCK. Using concentrations of 2‐NAP up to 21 mg kg −1 , identical observations were made (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat and pig, peripheral injections of 2-NAP abolish the satiating effect of peripherally injected CCK (Ebenezer and Baldwin, 1995;Baldwin et al, 1994). 2-NAP unlike devazepide has no effect on the intake of test meals nor does it eliminates the reduction of food intake produced by intracerebroventricular injections of CCK-8S.…”
Section: Discussionmentioning
confidence: 94%